Phylogenetic classification of the world’s tropical forests - Slik, J.W.F.; Franklin, J.; Arroyo-Rodríguez, V.; Field, R.; Aguilar, S.; Aguirre, N.; Ahumada, J.; Aiba, S-I.; Alves, L.F.; Anitha, K.; Avella, A.; Mora, F.; et al. (National Academy of Sciences, 2018)
Identifying and explaining regional differences in tropical forest dynamics, structure, diversity, and composition are critical for anticipating region-specific responses to global environmental change. Floristic classifications are of fundamental importance for these efforts. Here we provide a global tropical forest classification that is explicitly based on community evolutionary similarity, resulting in identification of five major tropical forest regions and their relationships: ( i ) Indo-Pacific, ( ii ) Subtropical, ( iii ) African, ( iv ) American, and ( v ) Dry forests. African and American forests are grouped, reflecting their former western Gondwanan connection, while Indo-Pacific forests range from eastern Africa and Madagascar to Australia and the Pacific. The connection between northern-hemisphere Asian and American forests is confirmed, while Dry forests are identified as a single tropical biome.